How Does Financial Instability in Lebanon Affect Purchasing Power? In-depth Analysis - Ahmad, Mayada; Jammal Naji (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2024)
The article thoroughly explores the significant impact of financial instability on purchasing power across all sectors in Lebanon. While inflation resulting from currency fluctuations drives up the costs of essential goods, economic uncertainty undermines incomes. Through a review of existing literature, presentation of a mathematical model, and proposal of mitigation strategies, the article aims to address these adverse effects. Practical solutions, ranging from enhancing financial education to fostering a resilient local economy, are considered to aid individuals in navigating this complex scenario and restoring a basic level of financial stability. In our study, we employed a combination of statistical methods, including the Multiple Regression Model and correlation analysis, to effectively identify the impact of financial instability on purchasing power in Lebanon. Through these techniques, our goal was to gain a comprehensive understanding of the relationship between purchasing power, inflation, and incomes, shedding light on how changes in financial stability might affect purchasing power in Lebanon.